'Take up the Man and lay down the Boy': Defining Rural Childhood in Northern Scotland during the Enlightenment. Issue 1 (May 2021) - Ritchie, Elizabeth; Bruce, Neil; Barton, Helen; Bockoven, Jaime; Taylor, Hayley
Abstract : Despite the theorising of Enlightenment and Romantic thinkers, no crystallised notion of childhood was particularly widespread or applied in the rural north. However, the evidence does suggest gradual phases, contingent on class, gender and circumstance, which tended to commence between the ages of five and eight and were distinguished by formal education or starting to assist in the family economy in a meaningful way. At the other end of childhood, taking up full-time employment or leaving home to work, study or marry therefore tended to be the rite of passage through which youngsters entered either adolescence or adulthood, but the ages at which this happened were highly circumstantial. The evidence suggests that there was no widespread dominant notion of childhood as a distinct life stage requiring specialised care and attention in rural communities during the period in which it was becoming established among theorists and the urban middle classes. For most the daily realities of labour, challenging economic circumstances, densely populated households, let alone the upheavals of clearance and emigration that affected so many, meant there was little time, energy or mental and emotional space to absorb and implement new philosophies. Rather, the needs of families meant that continuing older practices of gradually increasing responsibilities and responding to circumstances made most sense among the thatched longhouses and blackhouses of Scotland's rural north.